Oil-yielding Non-timber Plants Seeds: A Review on their Application for Health Care Products - Panta, Prasamsha; Khanal, Asmita; Shrestha, Sabina; Adhikari, Rameshwar (Current Traditional Medicine, 2024)
Oil-yielding non-timber forest products (NTFPs), such as Diploknema butyracea (Roxb.) H. J. Lam, Saipindus mukurossi Gaertn, and Hippophae salicifolia L. are widely distributed throughout Nepal and have traditionally been used as medicines by the locals since ancient times. Extensive scientific studies have demonstrated a wide range of benefits of these plants, which can have multiple uses in the pharmaceutical, cosmeceutical, and food industries. The potential of the plants, however, has not been fully explored, and they are, thus, minimally used only by locals. These plants have the potential for the development of several value-added products, leading to commercialization. This paper aims to explore in detail the health benefits and economic values of these plants to review the entrepreneurial aspects, improved farming and processing, and value addition in the product.
Keywords: economic value